2020
DOI: 10.1177/1071100720931095
|View full text |Cite
|
Sign up to set email alerts
|

Anterocentral Portal in Ankle Arthroscopy

Abstract: Background: The anterocentral portal is not a standard portal in anterior ankle arthroscopy due to its proximity to the anterior neurovascular bundle. However, it provides certain advantages, including a wide field of vision, and portal changes become redundant. The purpose of this study was to evaluate the neurovascular complications after anterior ankle arthroscopy using the anterocentral portal. Methods: We retrospectively identified patients who had undergone anterior ankle arthroscopy with an anterocentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…These results were comparable with those of our study, in which the mean distance was 2.2 mm and direct contact occurred in 40% of cases. In contrast, Stotter et al 30 recommended using an AC portal because of its broad visualization and low rate of neurovascular injury in the clinical setting. The present study showed that the MM portal had a longer distance from the neurovascular bundle and almost the same visibility as the AC portal.…”
Section: Discussionmentioning
confidence: 99%
“…These results were comparable with those of our study, in which the mean distance was 2.2 mm and direct contact occurred in 40% of cases. In contrast, Stotter et al 30 recommended using an AC portal because of its broad visualization and low rate of neurovascular injury in the clinical setting. The present study showed that the MM portal had a longer distance from the neurovascular bundle and almost the same visibility as the AC portal.…”
Section: Discussionmentioning
confidence: 99%
“…Such procedures are usually performed through two classic portals: the anteromedial (AM) portal and the anterolateral (AL) portal. The superficial peroneal nerve (SPN) is one of the most frequently injured structures during ankle arthroscopy, specifi-cally occurring when the AL portal is performed (5,6) . On the other hand, the deep peroneal nerve (DPN) is rarely injured during ankle arthroscopy.…”
Section: Introductionmentioning
confidence: 99%